Genetic and Environmental Variances of Bone Microarchitecture and Bone Remodeling Markers: A Twin Study. (16th February 2015) - Bjørnerem, Åshild; Bui, Minh; Wang, Xiaofang; Ghasem‐Zadeh, Ali; Hopper, John L; Zebaze, Roger; Seeman, Ego
ABSTRACT: All genetic and environmental factors contributing to differences in bone structure between individuals mediate their effects through the final common cellular pathway of bone modeling and remodeling. We hypothesized that genetic factors account for most of the population variance of cortical and trabecular microstructure, in particular intracortical porosity and medullary size – void volumes (porosity), which establish the internal bone surface areas or interfaces upon which modeling and remodeling deposit or remove bone to configure bone microarchitecture. Microarchitecture of the distal tibia and distal radius and remodeling markers were measured for 95 monozygotic (MZ) and 66 dizygotic (DZ) white female twin pairs aged 40 to 61 years. Images obtained using high‐resolution peripheral quantitative computed tomography were analyzed using StrAx1.0, a nonthreshold‐based software that quantifies cortical matrix and porosity. Genetic and environmental components of variance were estimated under the assumptions of the classic twin model. The data were consistent with the proportion of variance accounted for by genetic factors being: 72% to 81% (standard errors ∼18%) for the distal tibial total, cortical, and medullary cross‐sectional area (CSA); 67% and 61% for total cortical porosity, before and after adjusting for total CSA, respectively; 51% for trabecular volumetric bone mineral density (vBMD; all p  < 0.001). For the corresponding distal radius traits, genetic factors accounted for 47% to 68% of the variance (all p ≤ 0.001). Cross‐twin cross‐trait correlations between tibial cortical porosity and medullary CSA were higher for MZ ( r MZ  = 0.49) than DZ ( r DZ  = 0.27) pairs before ( p  = 0.024), but not after ( p  = 0.258), adjusting for total CSA. For the remodeling markers, the data were consistent with genetic factors accounting for 55% to 62% of the variance. We infer that middle‐aged women differ in their bone microarchitecture and remodeling markers more because of differences in their genetic factors than differences in their environment. © 2014 American Society for Bone and Mineral Research.